1991
DOI: 10.1128/jvi.65.2.996-1001.1991
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus (EBV) glycoprotein gp350 expressed on transfected cells resistant to natural killer cell activity serves as a target antigen for EBV-specific antibody-dependent cellular cytotoxicity

Abstract: Cell surface-associated viral glycoproteins are thought to play a major role as target antigens in cellular cytotoxicity and antiviral immunosurveillance. One such glycoprotein is the Epstein-Barr virus (EBV)-encoded glycoprotein 350 (gp350), which is expressed on both virion envelope and EBV producer cells and carries the virus attachment protein moiety. Although it is known that some antibodies to gp350 can neutralize the virus, the role of this glycoprotein in EBV-specific cellular cytotoxicity is not yet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…Our data support that Ab-dependent activation enhances the NK cell response to EBV-infected B cells and may have an important role in the control of this herpesvirus infection following the development of the T and B cell adaptive response. In agreement with previous reports (26), the presence of the gp350 envelope Ag on the surface of infected cells was associated with the ability of serum Abs to trigger NK cell degranulation and cytokine production. Ab-dependent activation was preferentially directed against AKBM cells in the lytic cycle, as previously reported for the direct NK cell response (9).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data support that Ab-dependent activation enhances the NK cell response to EBV-infected B cells and may have an important role in the control of this herpesvirus infection following the development of the T and B cell adaptive response. In agreement with previous reports (26), the presence of the gp350 envelope Ag on the surface of infected cells was associated with the ability of serum Abs to trigger NK cell degranulation and cytokine production. Ab-dependent activation was preferentially directed against AKBM cells in the lytic cycle, as previously reported for the direct NK cell response (9).…”
Section: Discussionsupporting
confidence: 92%
“…In addition to their direct interaction with target cells, which involves an array of inhibitory, activating, and costimulatory receptors, NK cells are the main effectors of Ab-dependent effector mechanisms triggered by FcgR-IIIA (CD16). Early studies identified ADCC as a mechanism of immune response to EBV-infected cells (24)(25)(26), and this issue has been re-explored in detail in this study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Several components of the immune system contribute to the highly efficient control of virus replication and proliferation of immortalized EBV-infected cells in healthy individuals. NK cells as well as antibody-dependent cellular cytotoxicity mechanisms directed against the viral glycoprotein gp350/220 seem to play a role (24,43); neutralizing antibodies prevent endogenous reinfection through virus particles released by epithelial cells or lymphocytes. The best-characterized and probably the most important components of these mechanisms, however, are HLA-restricted specific cytotoxic T lymphocytes (CTL) directed against viral gene products of the latent state.…”
mentioning
confidence: 99%
“…Epstein-Barr virus (EBV) is a ubiquitous human herpesvirus which causes infectious mononucleosis (IM) and is strongly associated with a number of malignancies, including endemic Burkitt's lymphoma (BL), undifferentiated nasopharyngeal carcinoma (NPC), and other lymphoproliferative diseases (25). Antibodies specific to gp340, the major EBV envelope glycoprotein and receptor ligand (32,41), are functionally active in a number of in vitro assays which include virus neutralization, complement fixation, and antibody-dependent cellular cytotoxicity (3,10,22,(34)(35)(36)42). Such antibodies would appear to provide a large proportion of EBV-specific serum humoral immunity in asymptomatic EBV-seropositive individuals and may therefore have an important role to play in limiting virus spread in vivo.…”
mentioning
confidence: 99%